2019
DOI: 10.1002/anie.201903252
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of the C−H Bond in Methane by Single Platinum Atomic Anions

Abstract: Mass spectrometric analysis of the anionic products of interaction between platinum atomic anions,P t À ,a nd methane,CH 4 and CD 4 ,inacollision cell shows the preferred generation of [PtCH 4 ] À and [PtCD 4 ] À complexes and al ow tendency toward dehydrogenation. [PtCH 4 ] À is shown to be H À Pt À CH 3 À by as ynergy between anion photoelectron spectroscopya nd quantum chemical calculations,i mplying the rupture of as ingle CÀHb ond. The calculated reaction pathway accounts for the observed selective activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 72 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…Extensive studies have shown that the cations of a number of transition metals bind methane, and, especially, third-row transition metal cations (including Ta + ) were found to dehydrogenate a specific number of CH 4 molecules, with a simultaneous liberation of dihydrogen. Previously, the Ta + + CH 4 system has been probed experimentally by employing Fourier-transform ion-cyclotron-resonance (FT-ICR) mass spectrometery, ,, guided ion beam experiments, a flow-tube reactor, and dissociation spectroscopy, as well as has been investigated theoretically. ,, In comparison to single atoms, metal clusters may represent more realistic models of reactive centers, in particular as (gas-phase) models for under-coordinated sites of metallic surfaces . However, the findings of bare metal clusters mediating room-temperature methane activation are limited to a few noble metals, namely, Pt, Pd, , Au, and Rh clusters (as well as binary AuPd and AuPt clusters). The corresponding reactivity modes are distinct for the respective elements; in particular, we note that small cationic Au, Rh, and Pd clusters react with a CH 4 molecule without H 2 liberation (with the exception of Rh 2 + and Pd 3 + ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that the cations of a number of transition metals bind methane, and, especially, third-row transition metal cations (including Ta + ) were found to dehydrogenate a specific number of CH 4 molecules, with a simultaneous liberation of dihydrogen. Previously, the Ta + + CH 4 system has been probed experimentally by employing Fourier-transform ion-cyclotron-resonance (FT-ICR) mass spectrometery, ,, guided ion beam experiments, a flow-tube reactor, and dissociation spectroscopy, as well as has been investigated theoretically. ,, In comparison to single atoms, metal clusters may represent more realistic models of reactive centers, in particular as (gas-phase) models for under-coordinated sites of metallic surfaces . However, the findings of bare metal clusters mediating room-temperature methane activation are limited to a few noble metals, namely, Pt, Pd, , Au, and Rh clusters (as well as binary AuPd and AuPt clusters). The corresponding reactivity modes are distinct for the respective elements; in particular, we note that small cationic Au, Rh, and Pd clusters react with a CH 4 molecule without H 2 liberation (with the exception of Rh 2 + and Pd 3 + ).…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectral and photoelectron studies show that single atomic species and small ionic clusters often cause this activation, for example, the breaking of O–H bonds in water, breaking a C–H bond in methane, and altering the bond angle in carbon dioxide. These small atoms and ionic clusters can be viewed as reasonable approximations of active sites in the bulk material and as fundamental starting points to assess catalytic reactivity. Investigating the reactivity of highly uncoordinated small Ir n – clusters will lead to better understanding of reactive sites/reactivity at defects on bulk metal surfaces, although this study will not necessarily capture all ligands that are present on the bulk metal catalyst surface. Traditionally, studies performed by flowing the reactant gas over a premade surface of the catalyst or freezing the reactant gas and interacting the catalyst with its surface allow the observation of products formed from the catalysis of the small molecule, but these are complicated and expensive for current calculation methods.…”
Section: Introductionmentioning
confidence: 99%
“…We start our discussion with Pt – , which has the largest EA and has been used in the past to activate methane experimentally . We then move in decreasing EA order going to Ni, Pd, and Fe.…”
Section: Resultsmentioning
confidence: 99%
“…Their energetics obtained mainly with density functional theory have shown that an anionic catalyst has a significant contribution of reducing the energy requirements for the MTM pathway, especially in stabilizing the transition states. The first systematic experimental investigation of the Pt – potential in C–H activation belongs to Bowen et al Bowen’s work demonstrated the selective activation of a single C–H bond and cast doubt on the previously accepted inadequacy of Pt – in methane activation . His work is the first experimental evidence of the Pt – capability of activating the CH 4 molecule proven by mass spectroscopy data as well as computational study …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation